(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In this article the issues of mass development of the national type of martial arts - kurash, etc. through an integral national system, as well as their use as a tool of mass involvement of children and students in physical activity are considered.